PREFIX A- (a) CHANGE FROM MIDDLE TO MODERN CIREBONESE(A Case Study of Serat Catur Kanda as a Middle Cirebonese text and Nguntal Nagara as a Modern Cirebonese text) - Sri Wulandari, - (2011)
This study is entitled "Prefix a- (a) Change from Middle to Modern Cirebonese." It aims at investigating prefix a- change in Cirebonese by comparing the words containing prefix a- which was used in Middle and in Modern Cirebonese era, especially in the word-form change. The data are collected from two poem manuscripts: Serat Catur Kanda as a text representative of Middle Cirebonese era and Nguntal Nagara as a text representative from Modern Cirebonese era. Interview was also held to get further information about Cirebonese. To classify the data, AntConc 3.2.1 -corpus software- was used. In addition, qualitative descriptive was implemented. To analyze the data, the theory of Anuswara principles as proposed by Padmosoekotjo (1986) and the separation between prefix a- and nasals as proposed by Salana (2002) have been used. The research found twenty one (21) changes experienced by prefix a- between the existing prefix a- in Middle and Modern Cirebonese era. Those changes consist of twelve (12) changes which exist in Middle Cirebonese era but do not exist in Modern time. They are 1. In the tendency of ny-: 1.1 The Emergence of a- lugu, 1.2 Deletion and Substitution Phenomenon: n-, and 1.3 Anuswara Character of ny-, namely any-; 2. In the tendency of n-: 2.1 The Emergence of a- lugu, and 2.2 Anuswara Character of n-, namely an-; 3. In the Tendency of m-: 3.1 The Emergence of a- lugu, 3.2 Anuswara Character of m-, namely am-, and 3.3 Special Case; 4. In the Tendency of ng-: 4.1 The Emergence of a- lugu, 4.2 Deletion and Substitution Phenomenon: n-, 4.3 Anuswara Character of ng-, namely ang-, and 4.4 Deletion and Substitution Phenomenon: m-. There are five (5) changes which exist not only in Middle Cirebonese era, but also in Modern Cirebonese: 1. The Emergence of prefix ny-, 2. Deletion and Substitution Phenomenon: n- (for prefix n-), 3. Deletion and Substitution Phenomenon: m- (for prefix m-), 4. Double prefixes related to m-, 4. Double prefixes related to ng-, and 5. Deletion and Substitution Phenomenon: ng- (for prefix ng-). The last four (4) changes exist in Modern Cirebonese era are: 1. The use of prefix n- as the result of prefix a- combination with j as the first letter of the root/ base, 2. The emergence of nasal n- after prefix a- combines with s as the first letter of the root/ base, 3. The emergence of nasal n- after prefix a- combines with determiner, and 4. The use of nasal m- as the result of the combination between prefix a- and base/ root begun with vowel.